Consensus Statement of the European Urology Association and the European Urogynaecological Association on the Use of Implanted Materials for Treating Pelvic Organ Prolapse and Stress Urinary Incontinence - (:unkn) unknown (ELSEVIER, 2017)
Context: Surgical nonautologous meshes have been used for several decades to repair abdominal wall herniae. Implantable materials have been adopted for the treatment of female and male stress urinary incontinence (SUI) and female pelvic organ prolapse (POP). Objective: A consensus review of existing data based on published meta-analyses and reviews. Evidence acquisition: This document summarises the deliberations of a consensus group meeting convened by the European Association of Urology (EAU) and the European Urogynecological Association, to explore the current evidence relating to the use of polypropylene (PP) materials used for the treatment of SUI and POP, with reference to the 2016 EAU guidelines (European Association of Urology 2016), the European Commission's SCENIHR report on the use of surgical meshes (SCENIHR 2015), other available high-quality evidence, guidelines, and national recommendations. Evidence synthesis: Current data suggest that the use of nonautologous durable materials in surgery has well-established benefits but significant risks, which are specific to the condition and location they are used for. Various graft-related complications have been described-such as infection, chronic pain including dyspareunia, exposure in the vagina, shrinkage, erosion into other organs of xenografts, synthetic PP tapes (used in SUI), and meshes (used in POP)-which differ from the complications seen with abdominal herniae. Conclusions: When considering surgery for SUI, it is essential to evaluate the available options, which may include synthetic midurethral slings (MUSs) using PP tapes, bulking agents, colposuspension, and autologous sling surgery. The use of synthetic MUSs for surgical treatment of SUI in both male and female patients has good efficacy and acceptable morbidity. Synthetic mesh for POP should be used only in complex cases with recurrent prolapse in the same compartment and restricted to those surgeons with appropriate training who are working in multidisciplinary referral centres. Patient summary: Synthetic slings can be safely used in the surgical treatment of stress incontinence in both male and female patients. Patients need to be aware of the alternative therapy and potential risks and complications of this therapy. Synthetic mesh for treating prolapse should be used only in complex cases with recurrent prolapse in specialist referral centres. (C) 2017 European Association of Urology. Published by Elsevier B.V. All rights reserved.
Keywords: Mesh; Stress urinary incontinence; Pelvic organ prolapse; Consensus statement; VAGINAL TAPE-OBTURATOR; LAPAROSCOPIC COLPOSUSPENSION; SURGICAL-TREATMENT; FOLLOW-UP; COLPOCLEISIS; METAANALYSIS; GUIDELINES; SURGERY; PREVALENCE; CHILDBIRTH